The role of osteocalcin in regulation of glycolipid metabolism and muscle function in children with osteogenesis imperfecta - Zheng, Wen-bin; Hu, Jing; Zhao, Di-Chen; Zhou, Bing-Na; Wang, Ou; Jiang, Yan; Xia, Wei-Bo; Xing, Xiao-ping; Li, Mei (Frontiers in Endocrinology, 2022)
Objective: Osteoblasts are discovered to secrete hormones with endocrine effects on metabolism, and osteocalcin (OC) is the most abundant non-collagenous protein in bone. We investigate the relationship between serum OC levels and glycolipid metabolism and muscle function in children with osteogenesis imperfecta (OI). Methods: A total of 225 children with OI and 80 healthy controls matched in age and gender were included in this single center study. Serum levels of fasting blood glucose (FBG), triglyceride (TG), total cholesterol (TC), low- and high-density lipoprotein cholesterol (LDL-C, HDL-C) were measured by automated analyzers. Serum levels of fasting insulin (FINS) was measured using an automated electrochemiluminescence system. Serum levels of OC and undercarboxylated osteocalcin (ucOC) were measured by enzyme-linked immunosorbent assay. Grip strength and timed-up-and-go (TUG) test were measured. Bone mineral density (BMD) and body composition were measured using dual-energy X-ray absorptiometry. Results: OI patients had significantly higher body mass index (BMI), FBG, and HOMA-IR, but lower HDL-C levels, lower grip strength and longer TUG than control group (all P<0.05). Serum OC, ucOC levels, and ucOC/OC in OI type III patients were significantly lower than those in OI patients with type I and IV. Serum levels of OC, ucOC, and ucOC/OC were negatively correlated to BMI, FBG, insulin levels, and HOMA-IR (all P<0.05). The ratio of ucOC/OC was positively correlated to grip strength (r=0.512, P=0.036), lean mass percentage (%LM) of the total body and limbs, and negatively correlated to fat mass percentage (%FM) of the total body, %FM and fat mass index (FMI) of the trunk (all P<0.05). Conclusions: Obesity, glucolipid metabolic abnormalities, and reduced grip strength were common in children with OI. Circulating osteocalcin and ucOC may play an important role in the regulation of glucose metabolism, as well as the muscle function of children with OI.